“TEMAN ASIK WISATA” SISTEM INFORMASI DAN ADMINISTRASI DATA UNTUK AKSELERASI DATA STATISTIK KUNJUNGAN WISATA DI KOTA SURAKARTA - Sulistyaningrum, Terry (Sekolah Vokasi, Universitas Sebelas Maret, 2024)
The first step of this research is to analyze service and administration issues in the Surakarta tourism and marketing sector at the Surakarta City Culture and Tourism Office. Next, the information design planning is prepared in accordance with the flow that will be used as the basis for creating an information and administration system to speed up statistical data on tourist visits in the field of Surakarta tourism destinations and marketing at the Surakarta City Culture and Tourism Office. In general, office work or activities related to services in obtaining, recording, storing, analyzing and communicating information in agencies and companies definitely require technological information to complete work effectively and efficiently. The focus of this research is how to create an information system to make it easier to carry out activities to accelerate statistical data on tourist visits and to increase work effectiveness in the field of Surakarta tourism destinations and marketing at the Surakarta City Culture and Tourism Office. In this research, the design of a data acceleration information system was carried out using a hosting website managed by the Surakarta City Culture and Tourism Office with the address www.solocity.travel. The output of this research is an information and data administration system that can help speed up the data management process which has the advantage of fast, real time and accountable statistical data management. Keywords : Service, Administration, Data Acceleration